Vitellogenesis: Yolk Synthesis Process in the Black Tiger Shrimp (Penaeus monodon) - หิรัญสัจจาเลิศ, รชนิมุข (KKU Science Journal, 2013)
In decapod crustaceans including the black tiger shrimp (Penaeus monodon), the process of vitellogenesis, which yolk proteins are synthesized, transformed into smaller molecules, and taken into maturing oocytes, is a central feature of reproduction. An understanding of the vitellogenesis in the important aquatic species may leads to sustainable seed production control in the commercial scale. The recent advances in molecular biology and immunological techniques result in the update knowledge of vitellogenesis in decapod crustaceans. This article covers the current status of research on vitellogenin in Penaeus monodon and other decapod crustaceans, especially prawns and shrimp. The article will also review the mechanisms of vitellogenin synthetic controlled by endocrine regulator. Finally, the related aspects of oocytes development in female shrimp during vitellogenesis will be discussed.